2014
DOI: 10.5812/ircmj.21346
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage and Resistance Pattern of Multidrug Resistant Staphylococcus aureus Among Healthy Children in Kashan, Iran

Abstract: Background:Nasal carriage of Staphylococcus aureus is a substantial source of human infections. Detection and treatment of nasal carriage in children with methicillin-resistant and multidrug resistant S. aureus (MRSA and MDRSA, respectively) may be an important modality in prevention of infections.Objectives:This study determined the prevalence, antibiotic resistance patterns and risk factors for nasal carriage of MDRSA among healthy children.Patients and Methods:This cross-sectional study was carried out on 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
6
13
2
Order By: Relevance
“…This frequency is lower than those obtained in the previous studies. 3,[13][14][15] Meanwhile, our findings revealed that 46.7% of the isolates were MRSA, which is in agreement with the study of Dadashi et al (43.0%). 16 It has been noted that the prevalence of MRSA has increased from the year 2000, which partly explains the high prevalence of MRSA observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…This frequency is lower than those obtained in the previous studies. 3,[13][14][15] Meanwhile, our findings revealed that 46.7% of the isolates were MRSA, which is in agreement with the study of Dadashi et al (43.0%). 16 It has been noted that the prevalence of MRSA has increased from the year 2000, which partly explains the high prevalence of MRSA observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, from 60 S. aureus-positive isolates, 31.66% (19 cases) were MDR-positive. This result is consistent with a previous study in Kashan, Iran, that reported 26.3% of healthy children were nasal carriers of S. aureus, 29.3% were MDR-positive, and 35.9% were MRSA-positive (23).…”
Section: Discussionsupporting
confidence: 93%
“…In a similar survey done in 2019, the outbreak of MRSA in males was more than female [23]. In the present study, 31.66% of the isolates were positive MDR, similar to a research done in Kashan, IRAN, with a prevalence of 29.3% MDR [24].…”
Section: Discussionsupporting
confidence: 90%